EVALUATION OF ANTI-INFLAMMATORY POTENTIAL OF CELECOXIB-BASED NANOGEL - Km Priyanka, Sunil Gupta, Amarjeet Singh (South Eastern European Journal of Public Health, 2025)
The aim of study was the evaluation of anti-inflammatory potential of celecoxib-based nanogel. Animal House, Innovative College of Pharmacy plot no. 6, NP-2, Greater Noida provided rats (either sex) weighing 180-220g. All the rats were separately in 4 groups (n=6) as group 1 given normal saline each day, group 2 given carrageenan (2%) intradermally, group 3 given carrageenan (2%) + oxalgin nanogel (applied topically), and group 4 given carrageenan (2%) + NG2 for 21 days. The anti-inflammatory potential of nanogel was performed through carrageenan induced paw edema. Celecoxib was found soluble in ethanol, methanol, and insoluble in distilled water. Moreover, in contrast to disease control group, the Carrageenan (2%) + NG 2 treated rats showed the volume of left hind paw as 3.26±0.14mm and 3.17±0.25mm, respectively. As the results indicate that developed celecoxib nanogels exhibited significant anti-inflammatory activity. Significant inhibition was recorded in the celecoxib nanogel (NG2) when given with carrageenan. In conclusion, celecoxib nanogels might be much significant in reducing the inflammation and counter it. It suggests to study the mechanism of absorption of celecoxib nanogel. It also needed to further researchers to affirm its mode of action for anti-inflammatory response.